Adaptive Fuzzy Sliding Mode Control for a Class of Nonlinear System - Xue Xiao; Zheng Zheng; Dong Haobin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
For a class of nonlinear system with parameter perturbation and external disturbance, adaptive fuzzy control can be used to approach the system unknown functions to reduce the control input and the steady-state error. And an adaptive switch control gain whose adaptive law is decreasing function is designed to weaken the system chattering, the switch gain of estimate will increase on the basis of the original without decreasing with the elimination of interference. If system is interferenced many times. Against the shortcomings, this paper proposes an improved adaptive law that can weaken the system chattering effectively while maintaining the strong robustness. The simulation results by tests show that this method is correct and effective.